2011
DOI: 10.1007/s00345-011-0746-4
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic outcomes following radical prostatectomy with intraoperative cell salvage

Abstract: IOCS is safe for the management of blood loss during RP. At long-term follow-up, IOCS use was not associated with an increased risk of BCR or death. While it remains preferable to avoid any form of blood transfusion, we advocate for the use of IOCS in place of allogeneic blood. These conclusions are drawn from our study of the largest and longest followed cohort patients who received IOCS blood during RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…No adverse effects were detected in the patients who received salvaged blood and there was no significant difference in the survival rates between IOCS and non-IOCS groups [15,19,31,35]. The patients receiving IOCS were found to be at least equal or superior in terms of biochemical or pathological recurrence when compared to non-IOCS groups [15,19,30,32].…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…No adverse effects were detected in the patients who received salvaged blood and there was no significant difference in the survival rates between IOCS and non-IOCS groups [15,19,31,35]. The patients receiving IOCS were found to be at least equal or superior in terms of biochemical or pathological recurrence when compared to non-IOCS groups [15,19,30,32].…”
Section: Discussionmentioning
confidence: 55%
“…All these studies showed that reinfusion of salvaged blood could reduce ABT requirements while the clinical outcomes of the patients who received salvaged blood were the same as those who did not [13,17,33,34]. No adverse effects were detected in the patients who received salvaged blood and there was no significant difference in the survival rates between IOCS and non-IOCS groups [15,19,31,35]. The patients receiving IOCS were found to be at least equal or superior in terms of biochemical or pathological recurrence when compared to non-IOCS groups [15,19,30,32].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…There is, however, emerging evidence of the successful employment of autotransfusion in cancer surgery outside spine and orthopaedic surgery, namely gynaecological, 36 Overall Chen et al 22 Street et al 23 Sakaura et al 20 Bilsky et al 17 Tanaka et al 25 Xu et al 26 Holman et al 12 Broaddus et al 13 Berkefeld et al 15 Shi et al 16 Cho and Sung 24 Demura et al 27 Bauer et al 14 Schmidt et al 28 Olerud et al 11 Guzman et al 21 Manke et al 19 Abe gastrointestinal, 37 hepatobiliary 38 and urological cancer surgery. 39,40 However, there are no previous reports of the use of autotransfusion in spinal tumour surgery.…”
Section: Discussionmentioning
confidence: 99%